Load and stress analysis for the swash plate of an axial piston pump/motor - Norhirni, M.Z.; Abd Shukor, Mohd Hamdi; Nurmaya Musa, S.; Saw, L.H.; Mardi, N.A.; Hilman, N. (American Society of Mechanical Engineers (ASME), 2011)
In an axial piston pump design, the swash plate plays an important role in controlling the displacement of the pump, especially in a closed loop system. In this paper, the axial piston pump is incorporated into the design of a hydraulic regenerative braking system for hybrid vehicles. The pump in this configuration should function in dual mode, as a pump and as a motor. For this to occur, the swash plate should swing in two opposite directions. The swash plate presented in this paper is designed for stability and ease of control. Analytical analysis of torque and forces were conducted using MATLAB software to verify the motion of the swash plate. Furthermore, finite element analysis was also carried out to evaluate the rigidity and stress in the system. The analytical evaluation has shown that as the swash plate angle increases, the required control force and torque increase almost linearly. However, the change of the plate angle was found to have no effect on the force exerted on the X-axis and the torque exerted on the Z-axis. DOI: 10.1115/1.4004578